Glucosamine Sulphate Iontophoresis Versus Ultrasound on Functional Outcome in Subjects with Patellofemoral Osteoarthritis (International Journal of Physiotherapy, 2025)
Background: Patellofemoral osteoarthritis (PFOA) is a progressive joint condition commonly affecting middle-aged and elderly individuals. Given the substantial physical and financial burden it imposes, evaluating the effectiveness of conservative treatment methods is crucial. This study aimed to compare the functional outcomes of glucosamine sulphate iontophoresis and therapeutic ultrasound in individuals diagnosed with PFOA.Method: Thirty individuals diagnosed with knee osteoarthritis were randomly divided into two groups of fifteen participants each. Group A was treated with a combination of ultrasound therapy and strengthening exercises targeting the Vastus Medialis Oblique (VMO). In contrast, Group B received glucosamine sulphate iontophoresis alongside the same exercise protocol. Functional outcomes were measured using the WOMAC and 6-MWT over a 10-day intervention period.Results: Group A showed a significant improvement in WOMAC scores from 42.89 to 29.22 (p < 0.001) and 6MWT scores from 15.26 to 20.14 (p < 0.001). In Group B, the WOMAC scores changed from 50.22 to 48.09 (p < 0.001), and 6MWT scores slightly improved from 16.93 to 17.23 (p < 0.001). Inter-group comparisons indicated that Group A exhibited statistically superior functional gains.Conclusion: The combination of VMO exercise and ultrasound therapy proved to be more effective in improving functional outcomes in individuals with PFOA than the combination of VMO exercise and glucosamine sulphate iontophoresis.